Exploring opportunities to support mental health care using social media: A survey of social media users with mental illness. Issue 3 (20th October 2017) - Naslund, John A.; Aschbrenner, Kelly A.; McHugo, Gregory J.; Unützer, Jürgen; Marsch, Lisa A.; Bartels, Stephen J.
Abstract : Aim: Social media holds promise for expanding the reach of mental health services, especially for young people who frequently use these popular platforms. We surveyed social media users who self‐identified as having a mental illness to learn about their use of social media for mental health and to identify opportunities to augment existing mental health services. Methods: We asked 240 Twitter users who self‐identified in their profile as having a mental illness to participate in an online survey. The survey was in English and inquired about participants' mental health condition, use of social media for mental health and interest in accessing mental health programs delivered through social media. Results: Respondents from 10 countries completed 135 surveys. Most respondents were from the United States (54%), Canada (22%) and the United Kingdom (17%) and reported a psychiatric diagnosis of either schizophrenia spectrum disorder (27%), bipolar disorder (25%), major depressive disorder (16%) or depression (20%). Young adults age ≤35 (46%) were more likely to use Instagram ( P  = .002), Snapchat ( P  < .001) and their mobile phone for accessing social media ( P  < .001) compared to adults age 36 and older (53%). Most participants (85%) expressed interest in mental health programs delivered through social media, especially to promote overall health and wellbeing (72%) and for coping with mental health symptoms (90%). Conclusions: This exploratory study demonstrates the feasibility of reaching social media users with mental illness and can inform efforts to leverage social media to make evidence‐based mental health services more widely available to those in need.